Computers in Cardiology
DOI: 10.1109/cic.2002.1166804
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear dynamics of heart rate variability in athletes: effect of training

Abstract: Only few studies on heart rate variability (HRV) in athletes have been performed so far. Moreover most of the data were obtained from time or frequency analysis. The aim of the present work was to use methods of nonlinear dynamics to study heart rate variability in a young population consisting of athletes and a sedentary group, used as controls. ECG episodes lasting 10 min were recorded digitally in supine position in a group of 34 young subjects. Spectral analysis was performed with Fast Fourier transform (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…Only one protocol with controlled breathing showed a negative ES for the normalized HF, which was inconsistent with the same condition in the other study (Table ) . Both studies with rugby athletes showed a negative ES for HF in logarithmic scale . The ES showed that the protocol, the modalities of sport and the unit of measure both appeared to contribute for the controversial results found in the literature, especially in the frequency domain analyses.…”
Section: Resultscontrasting
confidence: 64%
See 4 more Smart Citations
“…Only one protocol with controlled breathing showed a negative ES for the normalized HF, which was inconsistent with the same condition in the other study (Table ) . Both studies with rugby athletes showed a negative ES for HF in logarithmic scale . The ES showed that the protocol, the modalities of sport and the unit of measure both appeared to contribute for the controversial results found in the literature, especially in the frequency domain analyses.…”
Section: Resultscontrasting
confidence: 64%
“…From seven protocols using the low and high absolute spectral power, only one showed a moderate positive ES (Table ) . Contrarily, five protocols using the logarithmic transformation to calculate the power in LF showed large positive ES (Table ) . Considering normalized LF, two protocols with free breathing found a consistent negative ES, whilst two protocols with controlled breathing showed ESs with opposite signals (Table ) …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations